Brain Endoscopy, a big neurosurgical revolution - Al-Ameri, Laith Thamer (AL-Kindy College Medical Journal, 2018)
Endoscopy is a rapidly growing field of Neurosurgery, it is defined as the applying of endoscope to treat different conditions of brain pathology within cerebral ventricular system and beyond it, endoscopic procedures performed by using different equipment and recording system to make a better visualization enhancing the surgeon's view by increasing illumination and magnification to look around corner and to capture image on video or digital format for later studies.